Globalization, product differentiation and wage inequality - Bastos, Paulo (2010)
This paper develops a two-country, general equilibrium model of oligopoly in which the degree of horizontal product differentiation is endogenously determined by firms' strategic investments in product innovation. Consumers seek variety and product innovation is more skill intensive than production. Greater import competition increases innovation incentives, and thereby the relative demand for skill. An intraindustry trade expansion following trade liberalization can therefore increase wage inequality between skilled and unskilled workers. In addition, since product differentiation is resource consuming, freer trade entails a potential trade-off between production and variety. The import competition effect highlighted by the model, which plays a key role in determining the general equilibrium, is supported by panel data on Chilean manufacturing plants.